2000
DOI: 10.1136/ard.59.8.647
|View full text |Cite
|
Sign up to set email alerts
|

Healing of erosions in rheumatoid arthritis

Abstract: Reports on healing of erosions in rheumatoid arthritis are rare. However, it is expected that repair of erosions should be seen more often during the period of extensive use of disease modifying antirheumatic drugs, especially in patients who experience sustained remission. Two such cases are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 12 publications
1
15
0
2
Order By: Relevance
“…The regression was not complete, and the total amount of regression was therefore v14%. Similar findings by other authors confirm these results (33). Although this means that the existing scoring systems should be modified, to be able to include improvements, it is still a fact that regression of erosion is a rare phenomenon, and that the original theory of irreversibility, although not completely true, still is almost true for historical cohorts.…”
Section: Radiographic Evaluation As An Outcome Measure In Rasupporting
confidence: 89%
“…The regression was not complete, and the total amount of regression was therefore v14%. Similar findings by other authors confirm these results (33). Although this means that the existing scoring systems should be modified, to be able to include improvements, it is still a fact that regression of erosion is a rare phenomenon, and that the original theory of irreversibility, although not completely true, still is almost true for historical cohorts.…”
Section: Radiographic Evaluation As An Outcome Measure In Rasupporting
confidence: 89%
“…Exercises with experts blindly reading conventional radiographs assessing them for the evidence of repair of erosions consistently indicated that repair of individual lesions can indeed occur 16 17. Small radiographic case series from Rau and Herborn,18 McCarty and Carrera,19 Jalava and Reunanen20 and Sokka and Hannonen21 also suggested the principal possibility of the repair of individual bone erosions. As virtually all of these patients were either treated with gold salts or disease-modifying antirheumatic drug (DMARD) combinations the authors concluded that effective control of inflammation is a prerequisite for inducing repair.…”
Section: Discussionmentioning
confidence: 95%
“…Two cases with filling-in and recortication after coming into remission with MTX and gold treatment, respectively, were demonstrated by Socca and Hannonen [38].…”
Section: History Of Publications On Healingmentioning
confidence: 93%